Association Between Obesity and Poor Prognosis in Patients Receiving Anlotinib for Advanced Non-Small Cell Lung Cancer - Xiong, Anning; Nie, Wei; Cheng, Lei; Zhong, Hua; Chu, Tianqing; Zhong, Runbo; Lu, Jun; Wang, Shuyuan; Xu, Jianlin; Shen, Yinchen; Pan, Feng; Han, Baohui; et al. (Frontiers in Pharmacology, 2022)
Background: Anlotinib is a novel anti-angiogenesis drug. In non-small cell lung cancer (NSCLC), high body mass index (BMI) was not associated with worsesurvival in patients treated with bevacizumab compared with those with normal or low BMI. However, it remains unknown whether such an association still exist in NSCLC patients received anlotinib therapy. Hence, we conducted this study to investigate whether BMI is associated with clinical outcomes in patients treated with anlotinib for advanced NSCLC. Methods: Data of 554 patients from the ALTER-0302 and the ALTER-0303 trials were analyzed in this study. The patients were classified into non-obesity (BMI < 28 kg/m2) and obesity (BMI ≥ 28 kg/m2) subgroups. The primary endpoint was overall survival (OS). The secondary endpoints included progression-free survival (PFS), objective response rate (ORR) and disease control rate (DCR). OS was defined as the interval between the first drug administration and death. PFS was defined as the time span from the date of initiating the treatment to the first documented progression or death from any cause, whichever occurred first. ORR included complete response (CR) and partial response (PR). Results: There were 354 patients (63.9%) received anlotinib in this study. Restricted cubic spline model showed a U-shaped relation between BMI and the risk of death in anlotinib group. In a multivariable Cox regression model, a trend of worse overall survival was observed in obese patients received anlotinib compared with placebo (HR, 2.33; 95% CI, 0.77-7.06; P = 0.136). The interaction between BMI stratification and treatment was significant for OS (P for interaction = 0.038). Conclusions: Our results revealed a U-shaped relationship between BMI and risk of death in patients receiving anlotinib for advanced NSCLC. More importantly, obesity (BMI ≥ 28 kg/m2) might be a potential predictor of anlotinib in advanced NSCLC.